Por uma sociologia da produção e reprodução musical do presbiterianismo brasileiro: a tendência gospel e sua influência no culto - Dolghie, Jacqueline Ziroldo (2007)
The Brazilian Presbyterian service has assumed a fixed and peculiar form referring to its liturgical style. The exclusion of more ritualistic elements, as well as the conditions for their insertion, gave a very particular outline to the religious service in Brazil. Its shape can be reduced to two pillars: sermon and music. The music has also been developed in a peculiar manner within the denomination. Nevertheless, from the early 1990s, traditional music has been shaken with the fast-growing and consolidation of the gospel music market. Then, a new format of musical production related to congregational praise emerged in Brazil, which counteracting with the traditional productions due to its emotional and performatic aspect. This new model of congregational praise was totally accepted by young people and new converted ones because it was promoted by the specialized media and the gospel market and was in harmony with current cultural trends, somehow complicating the idea of preserving religious tradition. This fact occurred for many reasons, and among them, we can mention the appeal exerted by the musical market upon Presbyterian youth and the liturgica l role music played in this service, which has always created an atmosphere of religious frustration for some laic subgroups. Therefore, musical production and reproduction of Presbyterian service suffered modifications that can contribute directly to one of the biggest modifications which the Presbyterian service has suffered since its insertion in Brazil. This new model of congregational praise facilitated the rupture with the traditional hymnody, which has ever been weakened long ago. The present study deals with the modifications that occurred in Presbyterian liturgical music production and reproduction and the direct results on the religious service profile, as well as the motives that support those modifications on micro and macro social perspectives.(AU)